Andersen–Tawil Syndrome: A Comprehensive Review. Issue 4 (July 2021) - Pérez-Riera, Andrés Ricardo; Barbosa-Barros, Raimundo; Samesina, Nelson; Pastore, Carlos Alberto; Scanavacca, Mauricio; Daminello-Raimundo, Rodrigo; de Abreu, Luiz Carlos; Nikus, Kjell; Brugada, Pedro
Abstract : Andersen–Tawil syndrome (ATS) is a very rare orphan genetic multisystem channelopathy without structural heart disease (with rare exceptions). ATS type 1 is inherited in an autosomal dominant fashion and is caused by mutations in the KCNJ2 gene, which encodes the α subunit of the K + channel protein Kir2.1 (in ≈ 50–60% of cases). ATS type 2 is in turn linked to a rare mutation in the KCNJ5-GIRK4 gene that encodes the G protein-sensitive-activated inwardly rectifying K + channel Kir3.4 (15%), which carries the acetylcholine-induced potassium current. About 30% of cases are de novo/sporadic, suggesting that additional as-yet unidentified genes also cause the disorder. A triad of periodic muscle paralysis, repolarization changes in the electrocardiogram, and structural body changes characterize ATS. The typical muscular change is episodic flaccid muscle weakness. Prolongation of the QU/QUc intervals and normal or minimally prolonged QT/QTc intervals with a tendency to ventricular arrhythmias are typical repolarization changes. Bidirectional ventricular tachycardia is the hallmark ventricular arrhythmia, but also premature ventricular contractions, and rarely, polymorphic ventricular tachycardia of torsade de pointes type may be present. Patients with ATS have characteristic physical developmental dysmorphisms that affect the face, skull, limbs, thorax, and stature. Mild learning difficulties and a distinct neurocognitive phenotype (deficits in executive function and abstract reasoning) have been described. About 60% of affected individuals have all features of the major triad. The purpose of this review is to present historical aspects, nomenclature (observations/criticisms), epidemiology, genetics, electrocardiography, arrhythmias, electrophysiological mechanisms, diagnostic criteria/clues of periodic paralysis, prognosis, and management of ATS.